Overweight/obesity and socio-demographic disparities in children’s motor and cognitive function - Moss, Samantha; Zhang, Xiaoxia; Tamplain, Priscila; Gu, Xiangli (Frontiers in Psychology, 2023)
Fundamental motor skills (FMS) and cognitive function are important indicators of development in early childhood. Using a cross-sectional design, the purpose of this study was to investigate obesity (healthy weight vs. overweight/obese) and socio-demographic (i.e., gender, SES) disparities in FMS (locomotor and ball skills) and cognitive function (reaction time [RT] and movement time [MT]), in preschoolers. There were 74 preschoolers (girl = 38; Mage = 4.02 ± 0.73) recruited from two childcare centers and were categorized into healthy weight (n = 58, BMI percentile < 85%) and overweight/obese (n = 16, BMI percentile ≥ 85%) categories. Children’s FMS were assessed using the TGMD-3; cognitive function was assessed by the iPad-based CANTAB™ software using the Reaction Time Task (RTI), including reaction time (RT; Simple RT [SRT], choice RT [CRT]) and movement time (MT; simple MT [SMT], choice MT [CMT]). Children presented less FMS proficiency compared to recent data. Both weight groups performed comparably in FMS (ps > 0.05; ball skill Cohen’s d = 0.40; locomotor Cohen’s d = 0.02). Children in the overweight/obese group performed significantly worse on all cognitive tests compared to healthy weight peers (ps < 0.05; Cohen’s d range from −0.93 to −1.43). No significant gender or SES disparities were observed. Maintaining healthy weight status is critical for cognitive development among preschoolers, which may influence their developmental trajectory and school readiness.